The CFA Franc Zone and the EMU - Galy, Michel (IMF Working Papers; Working Paper, 1997)
Whether the prospective shift of the peg of the CFA franc to the euro would constitute an exchange rate arrangement with EMU countries would depend critically on the interpretation of the free convertibility of the CFA franc guaranteed by France. Nonetheless, this shift is likely to leave the CFA franc arrangements and operating features of the zone essentially unchanged. The current parity of the CFA franc could be considered in line with fundamentals. The potential economic consequences for the CFA franc countries could be positive over the long term, but there is a risk of a weakening of external competitiveness.